A Vibro-Acoustic Hybrid Implantable Microphone for Middle Ear Hearing Aids and Cochlear Implants - Ki Woong Seong; Ha Jun Mun; Dong Ho Shin; Jong Hoon Kim; Hideko Heidi Nakajima; Sunil Puria; Jin-Ho Cho (Sensors, 2019)
To develop totally implantable middle ear and cochlear implants, a miniature microphone that is surgically easy to implant and has a high sensitivity in a sufficient range of audio frequencies is needed. Of the various implantable acoustic sensors under development, only micro electro-mechanical system-type acoustic sensors, which attach to the umbo of the tympanic membrane, meet these requirements. We describe a new vibro-acoustic hybrid implantable microphone (VAHIM) that combines acceleration and sound pressure sensors. Each sensor can collect the vibration of the umbo and sound pressure of the middle ear cavity. The fabricated sensor was implanted into a human temporal bone and the noise level and sensitivity were measured. From the experimental results, it is shown that the proposed method is able to provide a wider-frequency band than conventional implantable acoustic sensors.